(untitled) (Itinera, 2024)
Alessandro Ferrara’s moral philosophy is centered on the concept of “exemplarity”, that is conceived of as an aesthetic notion. I aim to use this kind of approach, that I interpret relying on the reference to the inductive inference, in order to deal with the issues of the “cancel culture”.